Genetic Characterization of the Fish Piaractus brachypomus by Microsatellites Derived from Transcriptome Sequencing - Jorge, Paulo H.; Mastrochirico-Filho, Vito A.; Hata, Milene E.; Mendes, Natália J.; Ariede, Raquel B.; Freitas, Milena Vieira de; Vera, Manuel; Porto-Foresti, Fábio; Hashimoto, Diogo T. (Frontiers in Genetics, 2018)
The pirapitinga, Piaractus brachypomus (Characiformes, Serrasalmidae), is a fish from the Amazon basin and is considered to be one of the main native species used in aquaculture production in South America. The objectives of this study were: 1) to perform liver transcriptome sequencing of pirapitinga through NGS and then validate a set of microsatellite markers for this species; and 2) to use polymorphic microsatellites for analysis of genetic variability in farmed stocks. The transcriptome sequencing was carried out through the Roche/454 technology, which resulted in 3,696 non-redundant contigs. Of this total, 2,568 contigs had similarity in the non-redundant (nr) protein database (Genbank) and 2,075 sequences were characterized in the categories of Gene Ontology (GO). After the validation process of 30 microsatellite loci, 8 markers showed polymorphism. The analysis of these polymorphic markers in farmed stocks revealed that fish farms from North Brazil had a higher genetic diversity than fish farms from Southeast Brazil. AMOVA demonstrated that the highest proportion of variation was presented within the populations. However, when comparing different groups (1: Wild; 2: North fish farms; 3: Southeast fish farms), a considerable variation between the groups was observed. The FST values showed the occurrence of genetic structure among the broodstocks from different regions of Brazil. The transcriptome sequencing in pirapitinga provided important genetic resources for biological studies in this non-model species, and microsatellite data can be used as the framework for the genetic management of breeding stocks in Brazil, which might provide a basis for a genetic pre-breeding programme.